Multifunctional Flexible Humidity Sensor Systems Towards Noncontact Wearable Electronics - Lu, Yuyao; Yang, Geng; Shen, Yajing; Yang, Huayong; Xu, Kaichen (Nano-Micro Letters, 2022)
In the past decade, the global industry and research attentions on intelligent skin-like electronics have boosted their applications in diverse fields including human healthcare, Internet of Things, human–machine interfaces, artificial intelligence and soft robotics. Among them, flexible humidity sensors play a vital role in noncontact measurements relying on the unique property of rapid response to humidity change. This work presents an overview of recent advances in flexible humidity sensors using various active functional materials for contactless monitoring. Four categories of humidity sensors are highlighted based on resistive, capacitive, impedance-type and voltage-type working mechanisms. Furthermore, typical strategies including chemical doping, structural design and Joule heating are introduced to enhance the performance of humidity sensors. Drawing on the noncontact perception capability, human/plant healthcare management, human–machine interactions as well as integrated humidity sensor-based feedback systems are presented. The burgeoning innovations in this research field will benefit human society, especially during the COVID-19 epidemic, where cross-infection should be averted and contactless sensation is highly desired. Highlights: 1 This report summarizes recent advances of flexible humidity sensors and their integrated systems. 2 Typical examples of noncontact detections based on flexible and wearable humidity sensors are highlighted. 3 Research opportunities and challenges of pushing flexible humidity sensors towards practical contactless measurements are discussed.